2014
DOI: 10.1002/app.41083
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl chloride composites filled with olive stone flour: Mechanical, thermal, and water absorption properties

Abstract: The production of olive oil leads to considerable amounts of solid waste mainly composed of hard woody endocarp called olive stones. The aim of this work is to explore the possible use of ground olive stones as fillers for polyvinyl chloride (PVC), to elaborate a cost‐effective composite material with a solid loading of up to 50 wt %. After grinding, the ensuing olive stone flour (OSF) was incorporated into a PVC matrix via melt compounding and injection molding to elaborate PVC‐OSF‐based composites with a fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…It was found that the Young's modulus of the composite materials that incorporated a 5% MAPP, increased steadily with the percentage of reinforcement, this was the expected behavior, considering good fiber dispersion inside the matrix. A similar behavior was reported for ONF reinforced Polyvinyl Chloride composites [15]. On the other hand, the uncoupled composites showed a linear increase of the Young's modulus up to 40% fiber contents, then the value levelled or even fell down.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…It was found that the Young's modulus of the composite materials that incorporated a 5% MAPP, increased steadily with the percentage of reinforcement, this was the expected behavior, considering good fiber dispersion inside the matrix. A similar behavior was reported for ONF reinforced Polyvinyl Chloride composites [15]. On the other hand, the uncoupled composites showed a linear increase of the Young's modulus up to 40% fiber contents, then the value levelled or even fell down.…”
Section: Resultssupporting
confidence: 65%
“…However, WF imparted improvements in the impact strengths while OSF contributed to lower this property. The diminution on the impact properties was also observed in the case of ONF reinforced Polyvinyl Chloride [15]. Here again, the difference in the filler's morphology is on the origin of the disparity in the impact strength.…”
Section: Impact Strengthsupporting
confidence: 49%
See 1 more Smart Citation
“…These voids allow the accumulation of water at the interface between the particle and the matrix thus increasing the absorption capacity of the composites [78]. In addition, the increased contact between FF particles as their size and content in the matrix increases contributes to water absorption by capillarity due to the creation of a percolating path through the filler network [79]. It should be noted that the water absorption of FF waste is lower than that obtained from other agroforestry waste that has been used in similar amounts as reinforcements in thermosetting polymeric matrices, such as peanut shells [63] or palm kernel shell [80].…”
Section: Thermo-mechanical Propertiesmentioning
confidence: 99%
“…PVC is a polymer with low thermal stability, so easily degradable by dehydrochlorination around 100°C as a result of the formation of conjugated double bonds and polyene sequences . Naghmouchi et al studied PVC filled with olive stone flour . Blending polymers is an effective way to prepare new polymeric materials with better properties than virgin polymers .…”
Section: Introductionmentioning
confidence: 99%